Compassion satisfaction, compassion fatigue, anxiety, depression and stress in registered nurses in Australia: study 1 results - Hegney, Desley; Craigie, Mark; Hemsworth, D.; Osseiran-Moisson, Rebecca; Aoun, Samar; Francis, K.; Drury, V. (Blackwell Publishing, 2013)
Aim: To explore compassion fatigue and compassion satisfaction with the potential contributing factors of anxiety, depression and stress. Background: To date, no studies have connected the quality of work-life with other contributing and co-existing factors such as depression, anxiety and stress. Method: A self-report exploratory cross sectional survey of 132 nurses working in a tertiary hospital. Result: The reflective assessment risk profile model provides an excellent framework for examining the relationships between the professional quality of work factors and contributing factors within the established risk profiles. The results show a definite pattern of risk progression for the six factors examined for each risk profile. Additionally, burnout and secondary traumatic stress were significantly related to higher anxiety and depression levels. Higher anxiety levels were correlated with nurses who were younger, worked full-time and without a postgraduate qualification. Twenty percent had elevated levels of compassion fatigue: 7.6% having a very distressed profile. At-risk nurses' stress and depression scores were significantly higher than nurses with higher compassion satisfaction scores. Implications for nursing managers: The employed nurse workforce would benefit from a psychosocial capacity building intervention that reduces a nurse's risk profile, thus enhancing retention.